Ripping Off Some Room for People to "Breathe Together": Peer-to-Peer Education in Prison - Davis, Simone Weil (Social justice, 2015)
An essay is presented which discusses a learning model for education in the penal system involving the Walls to Bridges Collective group of incarcerated and non-incarcerated people and the Grand Valley Institute for Women in Kitchener, Ontario. Topics include peer-to-peer education as a method for prisoner-run college program, the importance of reciprocal learning between outside allies and faculty and educators inside the prison system, and prison postsecondary programs in the U.S. and Canada.